Clinical effect of day case arthroscopic surgery in tibial-eminence fracture in adults using button plates - Xu, Xiaohui; Wang, Huayi; Cui, Fengguo; Guo, Feng (Frontiers in Surgery, 2022)
BACKGROUND: The tibial-eminence fracture (TEF) is an anterior cruciate-ligament avulsion fracture with a low incidence. Many surgical techniques have been described, but none of them allow early functional exercise, and there are many postoperative complications. PURPOSES: This study aimed to evaluate the early clinical efficacy and complications of day case arthroscopic-surgery treatment of adult TEF with button plates. METHODS: We retrospectively analyzed patients with TEF treated with arthroscopic surgery. Clinical subjective evaluation included International Knee Documentation Committee (IKDC) subjective score, Lysholm Knee Score, and Visual Analog Scale (VAS) score. Knee joint scores were evaluated by Lysholm score. Clinical objective assessment included the Lachman test, anterior-drawer test (ADT), IKDC, and range of motion. We assessed patient quality of life using a life summary table. Assessment of fracture healing and internal fixation was based on lateral X-rays of the knee joint. We measured and evaluated patient satisfaction at the last follow-up in accordance with Marsh criteria. RESULTS: At final follow-up (average follow-up time, 28.36 ± 2.79 months), we evaluated results from 22 patients (22 knees). Average patient age during surgery was 33.64 ± 8.60 years. Average time from injury to surgery was 6.59 ± 2.22 h. Postoperative function was better than pre-operative function in all patients. IKDC subjective score, Lysholm score, and VAS score were better at final follow-up than before surgery. Differences in Lachman test and ADT scores before and after surgery were statistically significant. According to Intra-articular button position classification, 6 patients (6 knees) showed ideal position (A), 16 patients (16 knees) showed nearly ideal position (B), and none of the patients had nonideal position (C). The fractures of 22 patients healed completely; 2 patients had a 5°–10° knee joint dysfunction, and 1 had an abnormal knee sound. According to intra-articular button position classification, the rate of ideal position was 100%. Patient satisfaction rate was 81.8%. CONCLUSION: Day surgery using double-button plates to treat TEF could achieve anatomical reduction, power and stability, as well as good clinical efficacy.